A new species and a new synonym in the scarab genus Parastasia Westwood, 1841 (Coleoptera: Scarabaeidae: Rutelinae), with a key to species from Thailand - Hongsuwong, Thitipong; Sanguansub, Sunisa; Jaitrong, Weeyawat (Zootaxa, 2022)
Ten species of the genus Parastasia Westwood, 1841 including a new species and a new record are recorded from Thailand. We here describe Parastasia spinosa Hongsuwong, Sanguansub & Jaitrong, new species from eastern Thailand based on a male specimen. Parastasia bimaculata (Guérin-Méneville, 1843) is recorded for the first time in Thailand. We confirm that Parastasia bigibbosa Nonfried, 1891 occurs in the country. Parastasia andamanae (Ghai, Chandra & Ramamurthy, 1988) is synonymized with P. bigibbosa. A key to the Thai Parastasia species is provided.